2021
DOI: 10.1093/nar/gkab1213
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear poly(A) binding protein 1 (PABPN1) mediates zygotic genome activation-dependent maternal mRNA clearance during mouse early embryonic development

Abstract: An embryo starts its life with maternal mRNA clearance, which is crucial for embryonic development. The elimination of maternal transcripts occurs by the joint action of two pathways: the maternally encoded mRNA decay pathway (M-decay) and the zygotic genome activation (ZGA)-dependent pathway (Z-decay). However, zygotic factors triggering maternal mRNA decay in early mammalian embryos remain largely unknown. In this study, we identified the zygotically encoded nuclear poly(A) binding protein 1 (PABPN1) as a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…ZGA of the mice zygote embryos begins at the late 1-cell embryos, and many studies have pointed to the significance of chromatin remodeling in zygotic transcription initiation, including DNA methylation, histone modifications, chromatin accessibility, high-order chromatin structures formation, and RNA polymerase II (Pol II) binding [19][20][21][22] . Interestingly, in addition to the newly synthesized zygotic transcripts, ZGA-dependent maternal RNA clearance processes are crucial for early embryonic development 23,24 . Moreover, RNA metabolism during ZGA results in the heterogeneity of epigenomic modification among blastomeres and suggests transcriptome-wide regulation initiated at the 2-cell embryonic stage 25,26 .…”
mentioning
confidence: 99%
“…ZGA of the mice zygote embryos begins at the late 1-cell embryos, and many studies have pointed to the significance of chromatin remodeling in zygotic transcription initiation, including DNA methylation, histone modifications, chromatin accessibility, high-order chromatin structures formation, and RNA polymerase II (Pol II) binding [19][20][21][22] . Interestingly, in addition to the newly synthesized zygotic transcripts, ZGA-dependent maternal RNA clearance processes are crucial for early embryonic development 23,24 . Moreover, RNA metabolism during ZGA results in the heterogeneity of epigenomic modification among blastomeres and suggests transcriptome-wide regulation initiated at the 2-cell embryonic stage 25,26 .…”
mentioning
confidence: 99%
“…One such example is PABPN1. Zhao et al (2022) demonstrated that cytoplasmic PABPN1 is an early expressed zygotic factor and that it docks on uridylated transcripts and recruits 3 0 -5 0 exoribonuclease DIS3L2 to its targets, facilitating maternal mRNA decay (Zhao et al, 2022). Pabpn1 mRNA levels were significantly increased after fertilization and remained at a relatively high level until the eight-cell stage.…”
Section: Regulation Of Maternal Mrna Stabilitymentioning
confidence: 99%
“…All these factors are deposited in oocytes and are responsible for stage‐specific degradation of maternal mRNAs during M‐decay. Maternally expressed BTG4 and the CCR4‐NOT deadenylase complex continue to serve for Z‐decay, but likely require reinforcement from zygotic factors for timely removal of maternal mRNAs (Sha et al ., 2020 b ; Zhao et al ., 2022).…”
Section: Regulation Of Maternal Mrna Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse ZGA begins at the late 1-cell embryos, and many studies have pointed to the significance of chromatin remodeling in zygotic transcription initiation, including DNA methylation, histone modifications, chromatin accessibility, high-order chromatin structures formation, and RNA polymerase II (Pol II) binding [14][15][16][17] . Interestingly, in addition to the newly synthesized zygotic transcripts, ZGA-dependent maternal RNA clearance processes are crucial for early embryonic development 18,19 . Moreover, RNA metabolism during ZGA results in the heterogeneity of epigenomic modification among blastomeres and suggests transcriptome-wide regulation initiated at the 2-cell embryonic stage 20,21 .…”
Section: Introductionmentioning
confidence: 99%